Needs Analysis of English Skills amongst Electrical Engineering Students in ESP Contexts - Sarwanti, Sri; Sotlikova, Rima; Novianto, Dwi; Indriani, Lilia (Universitas Pendidikan Mandalika, 2023)
English is needed nowadays no matter what in global communication. In the ecucational context, English is neded to support the activites related to the ability in understanding the material and producing articles on the subject matter. The English skills of the electrical engineering students in Indonesia are generally unsatisfying. This study undercover the needs of English skills amongst Electrical Engineering students in Indonesian context. The study was conducted at Tidar University. The data were collected by using questionnaires and semi structured interviews. The results shows that the English skills needed by the Electrical Engineering students were grouped as receptive and productive skills. The receptive skills needed were the ability to grasp the texts’ ideas, the ability to listen to others’ words, The productive skills are the ability to produce the English eords to convey meanings in oral communications. The main points were greater technical vocabulary, grammatical structures, oral comprehension, and reading understanding.